(untitled) (Geo-Eco-Marina, 2019)
During the past five years, a team of Agrogeological Division of the Hungarian Geological and Geophysical Institute has studied the nutrient elements potential of the East-Hungarian sandy soils. Among these elements, the natural potassium sources are insufficient, i.e. neither the soil forming sediments, nor the groundwater cannot satisfy the consumption of the plants. Therefore, the unique K-source seems to be the meteoric water. The authors consulting more than three hundred geochemical, ecological, meteorological, astrophysical and radiological articles, identified the origin of atmospheric K-bearing aerosols Thus, in this paper, the K-salts, as the main aerosol particles in ice and rain nucleation, with stratospheric origin were discussed, mainly based on references. In the stratosphere, the solid particles show a well expressed stratification: aerosols from desertic, volcanic and anthropogenic origin are concentrated mainly at 20 km altitude, the cosmogenic particles are observable at 50–60 km, while the measurements prove a relatively uniform distribution of K bearing particles, decreasing abruptly in the troposphere, under cloud formation level. K-bearing aerosols form micron sized, soft flakes built up by very thin acicular crystals. They represent ideal nuclei for ice split and rain drop formation. Therefore, we suppose, that the stratospheric potassium is formed by cosmic radiation induced Ar/K reaction, the reverse of K/Ar decay. The increased K+ content in rainwater (or snow) samples above of highly populated centers is explained by the same Ar/K reaction, which is induced by low energy electromagnetic waves (UHF smog) due to (experimented) their Tunnel effect.